Assessing olive diversity for root traits associated with WUE - Bari A.; Boulouha B.; Sikaoui H.; Araus J.L.; Martín A.; González-Andujar J.L.; El Ibrahem A.; Talal A.; Hadjhasan A. (Drought management: scientific and technological innovations, 2008)
A plant's root system is a highly organized structure that not only serves as anchorage but also in the acquisition of water. As water resources are becoming limited water-use efficient genotypes with greater access to, and efficient exploitation of, sub-soil water are sought. However, measuring root traits to assess diversity within crops, is tedious work since this process involves studying large numbers of samples. To measure these root traits we used imaging techniques and quantitative modelling. The results show that there are indications of a relationship between root traits measured and stable carbon isotope discrimination (?), which is a surrogate for water use efficiency (WUE).
1. International Conference Drought Management: Scientific and Technological Innovations, 2008/06/12-14, Zaragoza (Spain)